2008
DOI: 10.1016/j.bbrc.2008.06.109
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of isolated ventricular myocytes from adult zebrafish (Danio rerio)

Abstract: The zebrafish is widely used for human related disease studies. Surprisingly, there is no information about the electrical activity of single myocytes freshly isolated from adult zebrafish ventricle. In this study, we present an enzymatic method to isolate ventricular myocytes from zebrafish heart that yield a large number of calcium tolerant cells. Ventricular myocytes from zebrafish were imaged using light and confocal microscopy. Myocytes were mostly rod shaped and responded by vigorous contraction to field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
92
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 17 publications
7
92
2
Order By: Relevance
“…Grunow et al (2011) and Mehnert et al (2013) showed previously that aggregates generated from larval trout have beat rates and action potential characteristics that closely match those of humans and that two commonly used hERG blockers, which are known to be pro-arrhythmic in humans, prolong action potentials in fish aggregates (Mehnert et al, 2013). Whilst we have not confirmed these findings in ZFHAs, our previous work (Brette et al, 2008) suggests ZF have a similar complement of cardiac ion channels to those of adult mammalian myocytes (Nemtsas et al, 2010) and hiPSC-CM (van den Heuvel et al, 2014). Thus, electrical activity between fish and humans is more similar than that between human and mouse, and, as such, ZFHA may be suitable for high/medium throughput pharmacological screening for human safety pharmacology (Brette et al, 2008;Nemtsas et al, 2010;Mehnert et al, 2013).…”
Section: Results and Discussion Generation Of Zfhascontrasting
confidence: 73%
See 3 more Smart Citations
“…Grunow et al (2011) and Mehnert et al (2013) showed previously that aggregates generated from larval trout have beat rates and action potential characteristics that closely match those of humans and that two commonly used hERG blockers, which are known to be pro-arrhythmic in humans, prolong action potentials in fish aggregates (Mehnert et al, 2013). Whilst we have not confirmed these findings in ZFHAs, our previous work (Brette et al, 2008) suggests ZF have a similar complement of cardiac ion channels to those of adult mammalian myocytes (Nemtsas et al, 2010) and hiPSC-CM (van den Heuvel et al, 2014). Thus, electrical activity between fish and humans is more similar than that between human and mouse, and, as such, ZFHA may be suitable for high/medium throughput pharmacological screening for human safety pharmacology (Brette et al, 2008;Nemtsas et al, 2010;Mehnert et al, 2013).…”
Section: Results and Discussion Generation Of Zfhascontrasting
confidence: 73%
“…Whilst we have not confirmed these findings in ZFHAs, our previous work (Brette et al, 2008) suggests ZF have a similar complement of cardiac ion channels to those of adult mammalian myocytes (Nemtsas et al, 2010) and hiPSC-CM (van den Heuvel et al, 2014). Thus, electrical activity between fish and humans is more similar than that between human and mouse, and, as such, ZFHA may be suitable for high/medium throughput pharmacological screening for human safety pharmacology (Brette et al, 2008;Nemtsas et al, 2010;Mehnert et al, 2013).…”
Section: Results and Discussion Generation Of Zfhascontrasting
confidence: 73%
See 2 more Smart Citations
“…Furthermore, the use of these SCC as a human drug test system has been described as their electrophysiological properties and their reaction to drugs are similar to human cardiomyocytes [8,9]. Fish cardiomyocytes could be an alternative because of their analogy to human heart electrophysiology [10][11][12].…”
Section: Introductionmentioning
confidence: 99%